The potential of several wild invasive fish species as fish-based organic fertilizers on the growth of two common vegetables in Malaysia - Jennifer Fabian Unggang; Mohd. Nizam Bakar; Ahmad Bukhary Ahmad Khair (Penerbit Universiti Kebangsaan Malaysia, 2023)
Three common invasive fish species in Malaysia, Peacock Bass (Cichla ocellaris), Nile Tilapia (Oreochromis niloticus) and Algae Suckermouth Catfish (Hypostomus plecostomus) were assessed for their efficacy as potential fish powder fertilizers. These invasive fish species were known to disturb the stability of lentic and lotic aquatic ecosystems in Malaysia, especially O. niloticus and H. plecostomus, altering aquatic habitats and food webs to be unsuitable for survival of indigenous fish species, while C. ocellaris becoming active aggressive predators on indigenous fish species, overall reducing indigenous fish species diversity. Plant primary macronutrient traces showed that C. ocellaris fish powder fertilizer recorded the highest Nitrogen (N) element percentage (15.81 ± 0.43 N %w/w) and trace Potassium (K) element (28,909.15 ± 32.56 K mg/kg), while H. plecostomus fish powder fertilizer recorded the highest trace Phosphorus (P) element (30,562.09 ± 197.11 P mg/kg). Plant secondary macronutrient traces showed that C. ocellaris fish powder fertilizer recorded the highest trace Magnesium (Mg) element (1496.66 ± 3.99 Mg mg/kg), while H. plecostomus fish powder fertilizer recorded the highest trace Calcium (Ca) element (6984.48 ± 26.20 Ca mg/kg). Two vegetable species tested for their growths, the water spinach (Ipomoea aquatica) and the spinach (Spinacia oleracea), showed that C. ocellaris fish powder fertilizer recorded the highest heights (263.74 ± 12.29 mm, 166.35 ± 9.46 mm), the widest leaf width (14.82 ± 0.66 mm, 21.08 ± 1.53 mm), and the widest stalk width (3.06 ± 0.10 mm, 2.89 ± 0.17 mm), respectively, comparable to the NPK 15:15:15 compound fertilizer, followed by H.plecostomus and O. niloticus fish powder fertilizers. C. ocellaris as predatory invasive fish species with the highest Mg concentration and moderate Ca concentrations, was especially suitable for the growth of both semi-aquatic and terrestrial vegetables grown on low Mg concentration soils.